ANALYSIS OF THE EFFECTIVESNESS OF ROTATING SHELF DESIGN ON DRESSING FRAME AT GRAHA ANANDA KINDERGARTEN, WEST BANDUNG - Sheila Andita Putri; Nurul Fitriana Bahri; Dandi Yunidar (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The development of fine motor skills, independence, and cognitive abilities are some important aspects that need to be stimulated in early childhood development. This study aims to analyze the effectiveness of rotating shelf design on dressing frame at Graha Ananda Kindergarten, West Bandung Regency. Based on the results of preliminary studies, it can be identified that there is a need to produce an ergonomic rotating shelf design to feature dressing frames that facilitate early childhood independence according to Montessori principles. The purpose of this study was to evaluate the performance and benefits of this rotating shelf design in supporting children's learning. The methodology used in this research is qualitative with a case study approach. Data collection techniques were carried out through observation and survey of the use of dressing frame with rotating shelf design at Graha Ananda Kindergarten. The observations focused on ease of access, practicality of use, and effectiveness in supporting early childhood independence. The results of this study show that the rotating shelf design provides convenience in retrieving and storing dressing frames, supports children's independent learning process, and strengthens fine motor and cognitive skills in early childhood. This research also shows that the design of the rotating shelf on the dressing frame contributes significantly in improving the accessibility and practicality of using the dressing frame at Graha Ananda Kindergarten. This design encourages the child's independence in using the tool, in accordance with Montessori principles, while strengthening the development of fine motor skills and understanding of the sequence of steps. The implications of this study underscore the importance of ergonomic design in supporting effective learning approaches at the early childhood development stage.